Church Administration Handbook - Powers, Bruce P. (Nashville, Tenn. Broadman & Holman Publishers, 1997)
All the basics for developing and implementing effective church administration in one volume. Good administration is essential to the mission of a church and the leadership of clergy and lay leaders. A smooth-running church can concentrate on spreading
Keywords: Church management -- Handbooks, manuals, etc. Church management